Socio-economic effects of the development of economic cooperation between Ukraine and the European Union for Poland - Shamborovskyi, Grigorii (Wydawnictwo Uniwersytetu Wrocławskiego, 2009)
This paper extends the computable general equilibrium model of the liberalization of foreign trade of integrated groups to a rich featuring economic welfare and the sectoral changes in Ukrainian, Polish and the EU economies. The GTAP model is used to explain the patterns of socio-economic effects in Poland when the EU and Ukraine remove barriers to trade. We parameterize the model to match the features of the European economic integration and analyze the changes of economic welfare in the Member States and potential candidate – Ukraine. The welfare measure evaluated is the change in equivalent variation. The results of our simulations suggest that the all analyzing economies will gain from liberalization trade between Ukraine and the EU. Economic welfare will rise by 508.38 million USD in Poland, 621.31 million USD in Ukraine and 6071.65 million USD in the EU.
Keywords: integracja gospodarcza; Unia Europejska; handel międzynarodowy; dobrobyt